2022
DOI: 10.3390/s22062294
|View full text |Cite
|
Sign up to set email alerts
|

Combating Single-Frequency Jamming through a Multi-Frequency, Multi-Constellation Software Receiver: A Case Study for Maritime Navigation in the Gulf of Finland

Abstract: Today, a substantial portion of global trade is carried by sea. Consequently, the reliance on Global Navigation Satellite System (GNSS)-based navigation in the oceans and inland waterways has been rapidly growing. GNSS is vulnerable to various radio frequency interference. The objective of this research is to propose a resilient Multi-Frequency, Multi-Constellation (MFMC) receiver in the context of maritime navigation to identify any GNSS signal jamming incident and switch to a jamming-free signal immediately.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…. (6) In practical computations, the optimal state estimation value can be obtained by setting ∂J L (X(k))/∂X(k) = 0 and utilizing the fixed-point iteration method, which maximally suppresses non-Gaussian outliers in the measurement vector [46].…”
Section: Mee Criterionmentioning
confidence: 99%
See 1 more Smart Citation
“…. (6) In practical computations, the optimal state estimation value can be obtained by setting ∂J L (X(k))/∂X(k) = 0 and utilizing the fixed-point iteration method, which maximally suppresses non-Gaussian outliers in the measurement vector [46].…”
Section: Mee Criterionmentioning
confidence: 99%
“…However, in narrow waterways and harbor areas, GNSS signals are subject to interference or obstruction by structures such as bridges, buildings, and harbor equipment, which do not satisfy the requirements of USV for GNSS signal robustness and accuracy [4][5][6]. Therefore, there is a need to enhance the tracking capability and robustness of GNSS receivers utilized in USVs to meet escalating navigation performance demands.…”
Section: Introductionmentioning
confidence: 99%
“…GNSS SDRs also offer greater flexibility and customization as compared to traditional GNSS receivers [2,5] by allowing developers to tailor GNSS solutions to specific requirements and integrate them into a wide range of devices and systems. GNSS SDRs also serve as a valuable tool for investigation, reproduction, validation and cross-verification of GNSS signals and by providing open platforms to explore and share raw recorded GNSS in-phase/quadrature (I/Q) datasets [3,4,7,8]. These features enable GNSS SDRs to offer flexibility, adaptability, customization and interoperability for innovation and research over hardware receivers.…”
Section: Introductionmentioning
confidence: 99%
“…Research addressing the three aspects mentioned above will greatly promote the application of real-time high-precision GNSS positioning in the mass market and advance autonomous driving and urban digitization. This Special Issue, entitled “ Advances in GNSS Positioning and GNSS Remote Sensing” in Sensors ( , (accessed on 2 February 2024)), attracted 10 articles [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] on new GNSS techniques for ionospheric studies, the impact of space weather on GNSS and methods for precise navigation.…”
mentioning
confidence: 99%
“…In their study, Islam et al [ 14 ] suggest the utilization of a jamming detector with multi-frequency and multi-constellation software that was able to define the GNSS receiver for Maritime Navigation in the Gulf of Finland. GPS-L5-only, Galileo-E5a-only, and Galileo-E5b-only signals and their multi-GNSS combination positioning results revealed that the Galileo-E5 and E5b signals performed better than other frequency bands in a maritime operational environment.…”
mentioning
confidence: 99%